Breaking of PT-symmetry in bounded and unbounded scattering systems - Ambichl, Philipp (2014)
PT-symmetric scattering systems with balanced gain and loss can undergo a symmetry-breaking transition in which the eigenvalues of the nonunitary scattering matrix change their phase shifts from real to complex values. We relate the PT-symmetry-breaking points of such an unbounded scattering system to those of the underlying bounded systems. In particular, we show how the PT thresholds in the scattering matrix of the unbounded system translate into analogous transitions in the Robin boundary conditions of the corresponding bounded systems. Based on this relation, we argue and then confirm that the PT transitions in the scattering matrix are, under very general conditions, entirely insensitive to a variable coupling strength between the bounded region and the unbounded asymptotic region, a result that can be tested experimentally and visualized using the concept of Smith charts.